Truncation of CYR1 promoter in industrial ethanol yeasts for improved ethanol yield in high temperature condition. (February 2018) - Hong, Kun-Qiang; Hou, Xiao-Yue; Hao, Ai-Li; Wang, Peng-Fei; Fu, Xiao-Meng; Lv, Ang; Dong, Jian
Graphical abstract: The CYR1 promoter was serially truncated from the 3′end by 30 bp steps to finely modulating the activity of Adenylate cyclase, encoded by CYR1 and synthesizing cAMP from ATP. The constructed mutants AY15a-90 and AY15a-120, whose promoters carry 90- and 120-bp truncations, showed a 2- and 3-fold drop in adenylate cyclase activity, and improved heat and ethanol tolerances than AY15a. Highlights: In the yeast Saccharomyces cerevisiae, the Ras-cAMP pathway plays an important role in regulating the stress response and growth. Adenylate cyclase is encoded by the CYR1 gene and plays the central role in the Ras-cAMP signalling pathway. Even if some methods about modifying CYR1 to obtain stress-tolerant mutants had been reported, mutants with too low adenylate cyclase activity could not be commercially used because of the low growth and metabolite rates. To determine an appropriate activity of adenylate cyclase, the CYR1 promoter was serially truncated from the 3′end by 30 bp steps in our study. This new strategy had been used for increased yeast stress tolerance and improved ethanol fermentation performance by finely modulating the expression of CYR1 in the yeast AY15 and also the yeast Saccharomyces cerevisiae background. Abstract: As the initiation of fermentation using the yeast Saccharomyces cerevisiae is always associated with a rapid drop in stress resistance, it is critical to develop yeast cells with elevated stress tolerances as well as normal growth and metabolite rates. In our study, the CYR1 promoter was serially truncated from the 3′end by 30 bp steps to finely modulating the activity of Adenylate cyclase, encoded by CYR1 and synthesizing cAMP from ATP. The constructed mutants AY15a-90 and AY15a-120, whose promoters carry 90- and 120-bp truncations, showed a 2- and 3-fold drop in adenylate cyclase activity, and improved heat and ethanol tolerances than AY15a. Interestingly, AY15a-90 and AY15a-120 also exhibited the same growth and fermentation rate as the strain AY15a. In very high gravity (VHG) fermentation at 40 °C, the yield of ethanol for AY15a-90 and AY15a-120 were 14% and 15% higher than that of AY15a, respectively. These results showed high stress tolerance and high fermentation activity could be compatible by finely modulating the expression of CYR1 .